Evaluasi Proses Bisnis Produksi Manufacturing Area 4 (SHINTA) Pada PT Tirta Investama (AQUA) Pandaan Menggunakan Metode Value Chain Analysis, Quality Evaluation Framework (QEF) dan Fault Tree Analysis (FTA) - Dicky Ilham Mualfi; Yusi Tyroni Mursityo; Nanang Yudi Setiawan (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
Tirta Investama Company (AQUA) Pandaan is a company that manufactures in the bottling of drinking water. In the process of drinking mineral water production, this company produces some brands in various kinds of the size, such as AQUA 5 Galloon, AQUA 220 ml, Mizone 500 ml, AQUA 600 ml, and AQUA 1500 ml. Manufacturing Area 4 (SHINTA) has cooperated with a manufacturing division which focuses on producing AQUA 600 ml. In the production process of AQUA 600 ml, it often experiences the achievement of activities that are not in accordance with the target of the company which can cause the achievement of production targets to go up and down based on the OE (Operational Efficiency) indicator on the PRS (Production Reporting System) information system. Based on these problems, it is necessary to evaluate the current production business processes. The first step is identifying business processes using the Value Chain Analysis method and modeling using Business Process Model and Notation (BPMN). The result will be an evaluation of the production business process using the Quality Evaluation Framework (QEF) method and known 16 quality factors with 4 quality factors that are not in accordance with the target company. The incompatibility of quality factors will be analyzed using the Fault Tree Analysis (FTA) method to find the root cause of the problem. FTA results from a quality factor mismatch are the skills of operators in recognizing the condition of machine parts differently and the level of product standards is higher.